Coronaviruses Pandemic And Food Industry - Complete Contingency Plan To Ensure Business Continuity And Safety Of People And Products - Aftais Ilham, Ismail IDRISSI, abdellah chahi, Kaoutar Bougouffa, Benchacho Mohamed, (International Journal of Advanced Science and Technology, 2020)
Modern lifestyle has seriously affected everyone’s eating habits and enforced many people to consume processed foods . Food plants should ensure the continuity of their activities using eventualite plans, these plans are the eventualite guaranty to ensure the persistence of the human-kind in such circumstances, No facility protection program is complete without clear, well-defined policies, and programs confronting the possible threat like coronaviruses pandemics.